The Cartoon guide to the Constitution of the United States - Lurio, Eric (New York Barnes & Noble Books, 1987)
The Constitution of the United States is 200 years old. Celebrate this special birthday by renewing your acquaintance with it in a lighthearted way. Sure, you can recite the Preamble, and you know about the three branches of government, and the Bill of Rights, but you may not remember, or you may never have known, how all this came to be. So let the Statue of Liberty be your tour guide through the Constitution, article by article, amendment by amendment. You'll have a good time. You'll also come away with a new appreciation for the special document the Founding Fathers created that hot summer in Philadelphia two centuries ago.
A gift of Dr. Victor T. Valbuena.
Keywords: American wit and humor, Pictorial; Constitutional law -- United States -- Caricatures and cartoons